The single transoral approach for Os odontoideum with irreducible atlantoaxial dislocation - Wang, Xiang (Springer-Verlag, 2009)
We report a 52-year-old female patient with a 2-year history of local neck pain, decreased cervical spine rotation, progressive numbness and weakness of both arms. Preoperative, dynamic X-rays, computed tomography, three-dimensional computed tomography demonstrated a displaced Os odontoideum with irreducible Subluxation of C1/2. We used a single transoral approach release, reduction using an assistance of skull traction, bone fusion and stabilization in the treatment of Os odontoideum with irreducible alantoaxial dislocation. Postoperative, the patient was free of all symptoms and X-rays taken showed a stable fusion of C1/2 at 6th postoperative month. This technique in the treatment of Os odontoideum with irreducible alantoaxial dislocation is atraumatic and effective. And preoperative dynamic X-rays, computed tomography, three-dimensional computed tomography and MRI scans provided an invaluable aid to select this operative procedure.